Financing Gender Equality: Budgets for Women's Policies in German and Austrian Länder. Issue 1 (1st March 2022) - Dursun, Ayse; Lang, Sabine; Sauer, Birgit
Abstract: State budgets reflect political priorities, providing a measure of issue relevance over time and comparatively across states. This article offers the first analysis of Länder budgets for women's policy agencies (wpa ) in Germany and Austria between 1991 and 2018. Comparing Länder wpa budgets provides insights into material allocations to, and the conditionality of, gender politics in Germany's strongly federalized state and Austria's weak federation. We find that German Länder budgeted for independent wpa earlier than Austrian Länder. However, with the advent of the 1999 Austrian coalition of Christian Democrats and the right-wing Freedom Party, which aimed to dismantle national-level gender policies, Austrian Länder investment in wpa grew to compensate for diminishing federal funds. The party constellation in power mattered more in Austria, but in both countries the parties in power were more important for wpa financing than the descriptive representation of women in Länder parliaments.